A closed-cycle miniature dilution refrigerator for a fast-cooldown 100 MK detector wafer test cryostat - Azzoni, S; May, AJ; Chase, ST; Coppi, G; Kenny, LC; Melhuish, SJ; Piccirillo, L; Suzuki, A; Wenninger, J (Springer, 2020)
The forthcoming generation of cosmic microwave background polarization observatories is developing large format detector arrays which will operate at 100 mK. Given the volume of detector wafers that will be required, fast-cooldown 100 mK test cryostats are increasingly needed. A miniature dilution refrigerator (MDR) has been developed for this purpose and is reported. The MDR is precooled by a doublestage 3He–4He Chase Research Cryogenics sorption refrigerator. The test cryostat based on this MDR will enable fast cooldown to 100 mK to support rapid feedback testing of detector wafers fabricated for the Simons Observatory. The MDR has been designed to provide a 100  mK stage to be retrocompatible with existing CRC10 sorption coolers, reducing the base temperature from 250 mK for the new generation of detectors. Other 250 mK cryostats can be retroftted in the same way. This confguration will meet the cryogenic requirements for single-wafer testing, providing 5–10 μW of cooling power at 100 mk for over 8 h. The system operates in a closed cycle, thereby avoiding external gas connections and cold o-rings. No moving parts are required, with the system operated entirely by heaters.